Design of an Ergonomic Prototype for Physical Rehabilitation of People with Paraplegia - Salazar, Franklin (2020)
Technology intervention within the field of physical rehabilitation allows to improve conventional processes and long-term results. Therefore, this research project proposes a design and implementation of an ergonomic device to exercise the upper and lower limbs of patients suffering from paraplegia, as part of their rehabilitation process. Despite attending conventional therapy sessions, the feeling of dissatisfaction is generalized by the need to complement these exercises. The general design of structure which includes the set of materials used, as well as the belt, power and control transmission systems. This design considers both weight of the structure exerted by gravity, as well as the exerted by the patient and the total dead load. In addition, the maximum stress analysis that supports the structure and the maximum deformation is carried out, taking into account that established safety factor is high. Experimental tests and surveys allow to corroborate the proper functioning and acceptance that this proposal has, given that its impact on rehabilitation process will be observed in long term. © Springer Nature Switzerland AG 2020.